Empowering Women as Family Financial Planners: A Mitigation of the Pandemic's Economic Impact - Fajri, Faridiah Aghadiati; Siregar, Hilda Octavana; Oktyawati, Dianila; Rumiyati, Rumiyati (UI Scholars Hub, 2003)
This article discusses a community engagement program that supports housewives as financial managers in difficult times, like COVID-19 Pandemic. This paper believes in the capacity of housewives, particularly in managing the financial conditions of the domestic. The pandemic conditions affect the world in multiple aspects and levels. Physical distancing as one of the policies applied had a wide impact, especially in the economic sector, globally and locally. The temporary shutdown of various business sectors has impacted the society, starting with a decrease in the family’s income, continuing with the difficulties to meet their needs, and eventually their welfare. This article studies the implementation of a community project in Sinduadi Village, Yogyakarta, Indonesia, focusing on family financial planning (FFP), which arguably can assist housewives to manage their finances during challenging periods. Starting from compiling materials for the introduction of the FFP application, the program was conducted through a series of training and discussion activities, setting forum for obtaining assistance from financial management experts. After the training, several domestic financial problems can be identified by the housewives, which help them to outline their priorities and thus make a better financial plan for the future.